Perspectives on election : five views - Cottrell, Jack W; Pinnock, Clark H; Reymond, Robert L; Talbott, Thomas B; Ware, Bruce A; Brand, Chad Owen (Nashville, Tenn. : Broadman & Holman Publishers, 2006)
Each author wrote a chapter, then each of the other authors wrote a response
Includes subject index and author index
Keywords: Predestination; Theology